Pengembangan Media Pembelajaran IPA Berbasis Game Edukasi Untuk Meningkatkan Minat Belajar - Anggreini, Nisah; Siregar, Zunaidy Abdullah; Machrizal, Rusdi (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The learning process is still carried out using manual methods, so students tend to get bored quickly when participating in learning activities in class. The aim of this research is to improve science learning outcomes by applying educational role playing learning methods to Class 7 students at SMPN 2 Ratu for the 2023/2024 academic year. This research was carried out at SMPN 2 Ratu, Labuhanbatu Regency, North Sumatra Province. The subjects in this research were 7th grade students of SMPN 2 Ratu, Labuhanbatu Regency, North Sumatra Province. This research is classroom action research with 2 cycles, each cycle consisting of 4 activities, namely planning, action, observation and reflection followed by planning in the next cycle by utilizing the results of previous reflection. The solution design in question is an action in the form of a role-playing learning method in teaching the subject of the Solar System for Class 7 SMPN 2 Ratu to 31 people. Research findings show that learning science using the educational role playing learning method can improve student learning outcomes as evidenced by the increase in science learning outcomes each cycle, namely from an average of 70.52 to an average of 80.19. students feel happy studying science in the field of biology with material on the greenhouse effect and are interested in learning.